Kaposi Sarcoma in people living with HIV: is it water under the bridge? - chiara papalini; Lucia Brescini; Laura Curci; Sabrina Bastianelli; Francesco Barchiesi; Andrea Giacometti; Daniela Francisci (Mediterranean Journal of Hematology and Infectious Diseases)
Kaposi Sarcoma (KS) is still common among people living with HIV (PLWH). A lot of literature illustrated risk factors associated with KS occurrence, while the aim of our study is to investigate possible factors influencing 5-year survival.